2011
DOI: 10.1111/j.1475-4932.2011.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Employment on Youth Overweight in Australia*

Abstract: Using data from the Household, Income and Labour Dynamics in Australia survey, this article seeks to estimate the causal effect of maternal labour supply on the body mass index and overweight status of older children in Australia. To achieve this aim, proxy variables, instrumental variables and sibling-difference models are used to account for the potential endogeneity of maternal employment. The results show that part-time or full-time work by the mother is associated with decreased excess body weight in yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Nevertheless, research on this topic has also been conducted in Australia (Bishop, 2011;Brown et al, 2010;Champion et al, 2012;Zhu, 2007), Canada (Baker and Milligan, 2008;Chia, 2008;Phipps et al, 2006), Japan (Gaina et al, 2009), the UK (Champion et al, 2012;Hawkins et al, 2007;Scholder, 2008), Denmark (Greve, 2011), Spain (Garcia et al, 2006), and in eight other European countries (Gwozdz et al, 2013). 3 For the purposes of this study, two insights from this research stream are particularly important.…”
Section: Prior Researchmentioning
confidence: 99%
“…Nevertheless, research on this topic has also been conducted in Australia (Bishop, 2011;Brown et al, 2010;Champion et al, 2012;Zhu, 2007), Canada (Baker and Milligan, 2008;Chia, 2008;Phipps et al, 2006), Japan (Gaina et al, 2009), the UK (Champion et al, 2012;Hawkins et al, 2007;Scholder, 2008), Denmark (Greve, 2011), Spain (Garcia et al, 2006), and in eight other European countries (Gwozdz et al, 2013). 3 For the purposes of this study, two insights from this research stream are particularly important.…”
Section: Prior Researchmentioning
confidence: 99%
“…This committee concludes that "although BMI does not measure body fat directly and therefore may lead to imprecise assessment of adiposity, it is feasible and has acceptable clinical validity if used thoughtfully" (Barlow et al, 2007, p. S167). More problematic, however, is that a number of studies (Bishop, 2011;Baker and Milligan, 2008;Chia, 2008;Garcia et al, 2006;Greve, 2011;Liu et al, 2009;Phipps et al, 2006;Zhu, 2007) use self-reported BMI, usually in the form of the children's height and weight as reported by their parents. There is considerable evidence that such self-reporting leads to large biases (e.g.…”
Section: Previous Researchmentioning
confidence: 99%
“…Research on this topic has also been conducted in Australia (Bishop, 2011;Brown et al, 2010;Champion et al, 2012;Zhu, 2007), Canada (Baker and Milligan, 2008;Chia, 2008;Phipps et al, 2006), Japan (Gaina et al, 2009) and the UK (Champion et al, 2012;Hawkins et al, 2007;Scholder, 2008), Denmark (Greve, 2011) and Spain (Garcia et al, 2006). This literature provides strong evidence for a positive effect of maternal employment on childhood obesity, although the magnitude of this effect varies substantially.…”
mentioning
confidence: 99%
“…126-129;Terza et al 2008). Note: all models include a full range of control variables comparable to model (5), Table 1; * p<0.10, ** p<0.05, *** p<0.01; Source: KiGGS 2003KiGGS -2006German Microcensus 1999, 2003, 2005, 2009 slightly larger estimates for maternal employment when taking the possible endogeneity of maternal employment into account (Anderson et al, 2003;von Hinke Kessler Scholder, 2008;Bishop, 2011).…”
Section: Estimates From IV Regressionsmentioning
confidence: 99%
“…The difficulty is to find strong instruments that additionally fulfill the validity assumption to be uncorrelated with the error term. In previous studies maternal employment is most often instrumented by local labor market conditions (Anderson et al, 2003;Greve, 2011;Bishop, 2011;Datar et al, 2014).…”
Section: Empirical Approachmentioning
confidence: 99%